2018
DOI: 10.1128/jvi.01896-17
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Inhibition of Host Gene Expression by Porcine Epidemic Diarrhea Virus nsp1

Abstract: Porcine epidemic diarrhea virus (PEDV), an enteropathogenic , has caused enormous economic losses in the pork industry. Nonstructural protein 1 (nsp1) is a characteristic feature of alpha- and betacoronaviruses, which exhibits both functional conservation and mechanistic diversity in inhibiting host gene expression and antiviral responses. However, the detailed structure and molecular mechanisms underlying the nsp1 inhibition of host gene expression remain unclear. Here, we report the first full-length crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 66 publications
1
53
0
Order By: Relevance
“…Subsequently, Western blot analysis indicated that nsp1(91-95sg) expression was significantly higher than nsp1 expression ( Fig. 2C), again demonstrating that nsp1 could inhibit its own expression (9,15). We examined Rluc mRNA expression in HEK-293T cells by real-time quantitative PCR and found that TGEV nsp1(91-95sg) and TGEV nsp1(37-40sg) did not inhibit Rluc mRNA synthesis at different time points ( Fig.…”
Section: Identification Of the Critical Region Of Tgev Nsp1 Required mentioning
confidence: 88%
See 3 more Smart Citations
“…Subsequently, Western blot analysis indicated that nsp1(91-95sg) expression was significantly higher than nsp1 expression ( Fig. 2C), again demonstrating that nsp1 could inhibit its own expression (9,15). We examined Rluc mRNA expression in HEK-293T cells by real-time quantitative PCR and found that TGEV nsp1(91-95sg) and TGEV nsp1(37-40sg) did not inhibit Rluc mRNA synthesis at different time points ( Fig.…”
Section: Identification Of the Critical Region Of Tgev Nsp1 Required mentioning
confidence: 88%
“…To identify which region in TGEV nsp1 was essential for its inhibitory activity, we used methods that have been previously used to study important functional regions in PEDV nsp1 (9). Based on the crystal structure of TGEV nsp1, we designed the following series of plasmids in which random coils were replaced with flexible Ser-Gly-Ser-Gly (sg) linkers: nsp1(1-3sg), nsp1(11-15sg), nsp1(19 -22sg), nsp1(37-40sg), nsp1(46 -48sg), nsp1(52-60sg), nsp1(66 -69sg), nsp1(76 -84sg), nsp1(91-95sg), and nsp1(105-109sg) (Fig.…”
Section: Identification Of the Critical Region Of Tgev Nsp1 Required mentioning
confidence: 99%
See 2 more Smart Citations
“…The TGEV nsp1 considerably suppresses host protein expression during viral infection [77]. Structural studies show that the core structure of PEDV nsp1 is highly similar to those of SARS-CoV nsp1 and TGEV nsp1 [183]. PEDV nsp1 inhibits host gene expression and three motifs (amino acids 67 to 71, 78 to 85, and 103 to 110) form a stable functional region for inhibition of host protein synthesis, differing considerably from SARS-CoV nsp1 [183].…”
Section: Pedv Nsp1mentioning
confidence: 99%